SWOT ANALYSIS OF THE INDONESIAN MEN'S NATIONAL FUTSAL TEAM MATCH IN THE 2022 ASIAN CUP QUARTER-FINAL MATC - Achmady, Achmady; Wismanadi, Himawan; Bawono, Mokhammad Nur; Suypriyanto, Catur; Wahyudi, Heri (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
The use of the SWOT (strength, weakness, opportunity, and threats) method is important in analyzing the factors that can cause failure. This method focuses on identifying the strengths, weaknesses, opportunities and threats of the Indonesian Futsal National Team in the quarter-finals of the 2022 Asian Cup. The methodology used is descriptive qualitative research which describes everything that happens in the video matches. Sources of information come from four licensed trainers. Data collection methods involve (1) interviews, (2) observation, (3) documentation. The research findings include, (1) strength includes: having a good attacking strategy, transitioning from offensive to defend or from defending to offensive that is compact, due to having good physical health, and also being accompanied by a competent coach when reading the character of the opponent's game and making decisions while the game is running. (2) Weaknesses include: lack of flying hours in the international arena, and also lowering the rhythm of the defend tempo to half the court after scoring the first goal so that the opposing team can dominate the match. (3) opportunity includes: the Indonesian team has a fifty-fifty chance when competing in the quarter-finals, with the mental support of the players 20% -30% will be maintained, but loses the moment in the last second which ends up losing the match. (4) threats include: threats received by the Indonesian team in terms of tactics are still losing because they still cannot escape from the opponent.